Echinochaete thailandica sp. nov. (Polyporaceae, Basidiomycota) from northern Thailand - Khyaju, Sabin; Bera, Ishika; Hyde, Kevin D.; Al-Otibi, Fatimah; Khongphinitbunjong, Kitiphong; Luangharn, Thatsanee (Phytotaxa, 2025)
The genus Echinochaete is a low-diversity genus within the family Polyporaceae, currently comprising only five taxonomically recognized species worldwide, suggesting the need for comprehensive revisionary studies. During a fungal survey in northern Thailand, a novel taxon was discovered, representing the first report of the genus. Here, we describe Echinochaete thailandica sp. nov., based on detailed morphological characteristics and two locus phylogenetic analyses (ITS and LSU). The new species is distinguished by lanceolate to cylindrical, longer (37–103 × 6–9 μm) setoid elements bearing lateral spines on the pileus, and cylindrical and large basidiospores (10.5–14.5 × 4.1–6.8 μm). Phylogenetic analyses position E. thailandica within the genus Echinochaete, distinct from all previously described taxa. This finding expands the known distribution of Echinochaete.